Digital marketing: does it impact on increasing the profit of MSMEs in Aceh? - Marjulin Marjulin (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
Modern market/consumer-oriented marketing concepts, or the marketing revolution manifested as an online marketplace, evolved in tandem with the rise of the internet. This study aims to develop knowledge by verifying whether the concept of using Digital Marketing in MSMEs in Aceh can increase operating profit. The methods used in this study are descriptive and explanatory research methods; the research is carried out to obtain a description, a systematic, factual and accurate picture of the facts, properties and relationships between the variables studied. This research method wants to get general answers about cause and effect by analyzing the factors causing phenomena in the concepts raised in this study; data will be collected by distributing questionnaires to MSME actors in the field. To obtain the results of this study, the data will be processed using statistical tools, namely simple linear regression. The results of this study show that using Digital Marketing in marketing its products can expand the market to increase the sales onset of MSMEs, so increasing sales will increase company profits. From the results of the research, it can be concluded that the increase in operating profit of which is influenced by the use of digital marketing by MSME players.